(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Linguistic variables are central to the study of sociolinguistics, as they capture variations in language based on social, geographical, and contextual factors. This study examines different types of linguistic variables, their role in language variation, and their impact on communication.